Cultura tributaria y cultura financiera en los trabajadores de la empresa Comercializadora San Juan SAC, periodo 2022 - Sandoval Conde, Katia (2023)
The tax culture and financial culture are two aspects of vital importance for a society to develop and grow sustainably, generating behavior oriented not only to voluntary compliance with its tax duties and obligations, but also making decisions on issues related to its finances. To avoid and prevent unnecessary over-indebtedness. The present investigation is entitled "Tax Culture and Financial Culture in the workers of the company Comercializadora San Juan SAC, period 2022", its objective is to determine the significant relationship that the workers present with respect to the tax culture and financial culture. The research was quantitative and correlational - descriptive design. After having analyzed the data, it was possible to determine that the tax culture and financial culture present a significant relationship, with its Rho Spearman correlation coefficient being 0.756 and its significance of 0.000.